(untitled) (Journal of Economics and Sustainability, 2020)
The inability of Nigeria to make its inflation rate a single digit motivates this study. This paper aims to empirically investigate whether inflation is solely caused by the increase in money supply beyond what is required by the economy, as maintained by monetarists using Nigerian data. Autoregressive Distributed Lag Model (ARDL) was used as the tool of econometric analysis on Nigerian time series data for 48 years. The ARDL was chosen because unit root tests were conducted. The results show that variables are not integrated in the same order. Money supply increment is demonstrated to be inflationary only in the short-run. The existence of other factors that influence inflation in the country is also evident. While money supply has no significant influence on inflation, the GDP and the constant have a significant influence on inflation in the long-run. Therefore, justification is provided for the myth of monetarist theory of inflation, claiming that money supply increment is a sole source of inflation, especially in Nigeria. Even though the result of the Wald test shows that the coefficients of money supply combined have a significant effect on inflation in conformity with the monetarist theoretical arguments, such effects are limited to short-run only. The findings of the research are limited to Nigeria whose data are used, based on ARDL as the econometrics techniques applied, for a period of 48 years from 1970–2017. Generally speaking, explanations for theories regarding inflation, especially in developing nations, should not be taken for granted. The research empirically demonstrates that the monetarist theory of inflation is a myth and not reality by using Nigerian data. It also suggests that other theories should be empirically tested to check which one best explain the nature of inflation dynamics in a country to proffer a better solution to a high inflation rate problem. Received 15 April 19. Revised 29 March 20. Accepted 2 April 20.